2023
DOI: 10.9734/ijecc/2023/v13i71890
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Response of Gladiolus (var. American Beauty) towards Plant Growth Regulators Using Cormel Explants

Abstract: Gladiolus is one of the most potential bulbous cut flower crops cultivated widely in India due to its attractive and long lasting spikes. The plant is propagated vegetatively through corms and cormels, but due to low rate of multiplication, its cultivation is hindered. Also, it is grown through underground modified stems, they are more often attacked by soil borne diseases such as Fusarium corm rot. In-vitro propagation techniques, assumes significance, especially for securing rapid multiplication of quality p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…According to a number of reports, cytokinin is required for shoot organogenesis [8,9,28,34,91] and encourages bud/shoot regeneration [53,64,87]. Among the cytokinins, benzyl aminopurine (BAP) or benzyladenine (BA) are important compounds that have been shown to have favorable benefits over other cytokinins [9,51,92,93]. However, variable doses of BAP have been standardized including higher doses of BAP that have been optimized for shoot proliferation, where BAP at 4 mg L −1 resulted in maximum shoot proliferation [9,31,51], while 3.0 mg L −1 BAP was found to be best for shoot proliferation [75], 2-3 mg L −1 BAP was found to have the most potential for gladiolus shoot induction, and a constant dose of 2 mg L −1 BAP has been recommended [93].…”
Section: Effect Of Plant Growth Regulatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to a number of reports, cytokinin is required for shoot organogenesis [8,9,28,34,91] and encourages bud/shoot regeneration [53,64,87]. Among the cytokinins, benzyl aminopurine (BAP) or benzyladenine (BA) are important compounds that have been shown to have favorable benefits over other cytokinins [9,51,92,93]. However, variable doses of BAP have been standardized including higher doses of BAP that have been optimized for shoot proliferation, where BAP at 4 mg L −1 resulted in maximum shoot proliferation [9,31,51], while 3.0 mg L −1 BAP was found to be best for shoot proliferation [75], 2-3 mg L −1 BAP was found to have the most potential for gladiolus shoot induction, and a constant dose of 2 mg L −1 BAP has been recommended [93].…”
Section: Effect Of Plant Growth Regulatorsmentioning
confidence: 99%
“…Among the cytokinins, benzyl aminopurine (BAP) or benzyladenine (BA) are important compounds that have been shown to have favorable benefits over other cytokinins [9,51,92,93]. However, variable doses of BAP have been standardized including higher doses of BAP that have been optimized for shoot proliferation, where BAP at 4 mg L −1 resulted in maximum shoot proliferation [9,31,51], while 3.0 mg L −1 BAP was found to be best for shoot proliferation [75], 2-3 mg L −1 BAP was found to have the most potential for gladiolus shoot induction, and a constant dose of 2 mg L −1 BAP has been recommended [93]. Some research reports, however, suggested lower BAP concentrations for shoot regeneration; one such report [94] found that 0.5 mg L-1 BA produced the best results, while [81] obtained better results at concentrations of BAP in the range of 0.5 to 1.0 mg L −1 .…”
Section: Effect Of Plant Growth Regulatorsmentioning
confidence: 99%
See 2 more Smart Citations